P53 alterations in bladder tumors from arsenic and tobacco exposed patients - Moore, Lee E. (2003)
Previous studies demonstrated that tobacco and arsenic exposure are risk factors for bladder cancer. A case-case study was conducted to compare p53 mutations in 147 bladder tumors from South American patients by tobacco and arsenic exposure. Information on residential history and lifestyle factors was collected. The prevalence of p53 mutations and protein expression was examined in relation to tumor stage, grade, patient age, gender, tobacco and arsenic exposure. Smokers were grouped as ever/never smokers and by pack years of exposure (0, 1-20, >20). Patients were also grouped into four arsenic exposure categories based on the average of the five highest years arsenic concentration in their drinking water: group 1, non-detectable to < 10 μg/l (n = 50); group 2, 10-99 μg/l (n = 31); group 3, 100-299 μg/l (n = 35); group 4, >300 μg/l (n = 30). The proportion of tumor samples with p53 mutations and P53 immunopositivity increased strongly with both stage and grade, but not with arsenic exposure or smoking. The prevalence of tumors containing mutational transitions increased markedly with tumor stage (from 14 to 52%, Ptrend = 0.005) and grade (from 11 to 48%, Ptrend = 0.004) and was higher in smokers than in non-smokers (34 versus 18%, respectively, P = 0.10). An increasing trend was observed with pack years of smoking (P = 0.09). The majority of mutations in tumors from both smokers and non-smokers were G → A transitions, however, in smokers a preference for G → A transitions at CpG sites was observed (P = 0.07, two-tailed) and a positive trend was observed with pack years of exposure (P = 0.04). A hotspot was found at codon 273 in 12% of the tumors from smokers but was not observed in never smokers (P = 0.05) and a positive trend was observed with pack years of tobacco exposure (P = 0.001). Neither stage nor grade demonstrated a preference for CpG site mutation, suggesting that these changes may be early exposure-related events in carcinogenesis and are not related to tumor progression. Arsenic exposure was not associated with an increased prevalence of p53 mutation or P53 immunopositivity and there was no evidence of interaction between arsenic and smoking with these outcome variables.